Psychotherapeutic Effect of Using Songs and Music for the Promotion of Basic Education Among Adult Learners: An Analysis - Olojede, Adeshina Abideen (European Scientific Journal, ESJ, 2020)
Various teaching methods and approaches have been researched and used in nonformal education, but the abstract technique of songs and music is uncommon. The peculiar characteristics of adult learners make teaching and learning to be complex. This study is experimental. Seventy-six (76) adult learners were purposefully selected and divided into two groups of thirty-eight (38) each. Group A was exposed to songs in both Nupe and English language over a period of time. Observation and narrative methods were used to study the effect of songs and music as a tool for the facilitating of learning among adults’ learners. The facilitators encouraged the learners to identify new words which were written separately on boards to spell and pronounce. Learners in Group B were exposed to the normal learning process of using primers to facilitate learning. At the end of one month, both groups were examined and evaluated. Data were analyzed using percentage. The results of the experiment showed that the learners in Group A exhibited more than 80.0% of success in assimilation as against Group B with 38% success when both were examined. 31 out of the 38 (81.5%) learners from Group A can identify and read fairly with little assistance while 14 learners from Group B (36.8%) can read in relation to music played and identification of words identified and written on board by the facilitator. Group A members were more enthusiastic to learn as they were involved in generating means of learning; they were able to identify words and produce sentences from the words written on the board. The study also showed that songs and music produce a psychotherapeutic effect that soothes the learning process and produce a positive outcome while teaching adult learners. The paper recommends the inclusion of local songs and music into the non-formal education curriculum. Also, facilitators should be more creative in the teaching and learning process of adult education.